The Effect of Leadership Style and Work Environment on Teacher Performance - Runi Linda Oktavia; Muhammad Yusuf; Hendra Suwardana (Universitas Muhammadiyah Gresik, 2022)
This research aims to determine the effect of leadership style and work environment on teacher performance at SMA Negeri 1 Paciran. This research is a quantitative research using a survey approach. The population in this research was 61 and the sample was 61 according to the population. The data collection instrument used a questionnaire with a Likert scale which had 5 alternative answers with 55 statement items which were analyzed using descriptive analysis and multiple regression analysis. The results of the descriptive statistical analysis test showed that (1) the principal's leadership style at SMA Negeri 1 Paciran was in the very good category, (2) the work environment at SMA Negeri 1 Paciran was in the good category, and teacher performance at SMA Negeri 1 Paciran was in the category good. The results of hypothesis testing indicate that simultaneously all independent variables have a significant effect on teacher performance, for the relationship between leadership style and work environment is the most dominant work environment on teacher performance.